Training and Employee Performance in the Privately Owned Enterprises in Uganda: A Case of Ntake Bakery Group of Companies - Isaac Ssemanda (Uganda Christian University, 2023)
The study investigated training and employee performance at Ntake Bakery Kampala Nalukologo. The objectives of the study were; I) To find out the training programs carried out, ii) To assess the effects of training on employee performance, iii) To find out the relationship between training and employee performance and iv) To establish factors that affect employee performance in Ntake Bakery. The study used cross-sectional research design in nature and this helped in collecting data from a wide section of study respondents. A sample of 51 employees at Bakery was used. Data was analyzed using frequencies and percentages were derived for easy interpretation and statistical tools like tables and figures were used. The findings on training programs indicate that management at Ntake Bakery does training needs assessment, training design and training evaluation though some of the activates under these training programs are not conducted for example during the evaluation tests are not given to the employees in the company that have attained training and also in training needs assessment the budgets are not drawn to cater for the training process. The findings indicated that training is a leading factor in employee performance of Ntake Bakery that is to say, training affects performance positively at Ntake Bakery in that. it increases productivity it enhances job satisfaction and increase knowledge and skills when performing the work. The findings showed that there are other factors that affect employee performance at Ntake Bakery besides training such as enough tools and equipment, clear organizational policies among others. Management should devise means of increasing the commitment of employees towards the training policy of the Bakery and also Management should take into consideration the rapid employee promoter score and competition from other Bakeries. It finally recommended that employers should always give the tests to employees that have attained training during evaluation to see if the training they conducted was effective. On the findings about the relationship between training and employee performance at Ntake Bakery.it was revealed that there is are positively relationship between training and employee performance at Ntake Bakery because the respondents agreed with the statement. In conclusion, the management of Ntake Bakery should ensure that they do all the activities that are under the training programs in order to achieve effective training leading to employee performance in the company.
This is a dissertation.